2013
DOI: 10.1128/jb.00482-13
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the ald Gene Encoding Alanine Dehydrogenase by AldR in Mycobacterium smegmatis

Abstract: A lanine dehydrogenase (EC 1.4.1.1; Ald) catalyzes the reversible oxidative deamination of L-alanine to pyruvate with the concomitant reduction of oxidized nicotinamide adenine dinucleotide (NAD ϩ ) to nicotinamide adenine dinucleotide phosphate (NADH). Its forward reaction appears to be necessary for the aerobic utilization of alanine as a nitrogen source in Mycobacterium tuberculosis, Mycobacterium smegmatis, and Mycobacterium bovis BCG (1-3). The reverse reaction of Ald was proposed to play a role in recycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
38
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(43 citation statements)
references
References 49 publications
3
38
1
Order By: Relevance
“…Other studies reported that expression of the ald gene was upregulated in Mycobacterium marinum during persistence within its host granulomas and in M. tuberculosis under nutrient starvation conditions (5, 15). Expression of the ald gene was demonstrated to be strongly induced in M. smegmatis and M. tuberculosis grown in the presence of alanine (2,3,14).…”
Section: Importancementioning
confidence: 99%
See 3 more Smart Citations
“…Other studies reported that expression of the ald gene was upregulated in Mycobacterium marinum during persistence within its host granulomas and in M. tuberculosis under nutrient starvation conditions (5, 15). Expression of the ald gene was demonstrated to be strongly induced in M. smegmatis and M. tuberculosis grown in the presence of alanine (2,3,14).…”
Section: Importancementioning
confidence: 99%
“…Other studies reported that expression of the ald gene was upregulated in Mycobacterium marinum during persistence within its host granulomas and in M. tuberculosis under nutrient starvation conditions (5, 15). Expression of the ald gene was demonstrated to be strongly induced in M. smegmatis and M. tuberculosis grown in the presence of alanine (2,3,14).Expression of the ald gene in M. smegmatis is under the control of the AldR transcriptional regulator that belongs to the Lrp/AsnC (leucine-responsive regulatory protein/asparagine synthase C) family. AldR is a direct sensor of alanine and serves as both an activator of ald expression in the presence of alanine and a repressor in the absence of alanine (14).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Incidentally, the latter is listed in one study as among the top three targets against persistence (Hasan et al, 2006). Recently, it has been reported that in a hypoxic model of M. smegmatis the expression of alanine dehydrogenase increases and is regulated by aldR (Jeong et al, 2013), a gene whose product is homologous to the current protein. We have purified and crystallized the protein in order to understand the molecular mechanisms that are fundamental to its regulatory activity.…”
Section: Introductionmentioning
confidence: 99%